Centro de formación infantil - Serpa Cózar, Ariana Elizabeth (2018)
The proposal was made in the workshop AR0960, which is presented as a main objective that has been migrated from La Mariscal so that it becomes a place within the area and in its periphery that generates new dynamics and environments for this population growth. Several centralities that will be the focal points of growth as new facilities that contribute and supply the new population density (27601 inhabitants) by the year 2040, thus covering the needs of the city. The search and response to the needs of the sector. The present work of the degree is a response to the needs of employees so that it can be developed from a vision for the future of a focus towards an optimal planning and urban design in the principles of training, development and Quality education for all direct and indirect users who are beneficiaries of the implementation of the equipment. This is why, through the analysis carried out in the study area, the direct objectives set and the strategies to solve the problem of creating a Child Training Center that responds adequately as well as the immediate environment and the activities that They are required for the development of children from 0 to 5 years old with methodologies in the development of the toddler and its direct relationship with the environment. Likewise, the Child Training Center will become an important space in the periphery of El Mariscal and will meet with the positive characteristics that promote the revitalization of this part of the city incorporating the activities within the same lot.